2015
DOI: 10.1371/journal.pone.0131804
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Allergy to Milk, Egg, Cod, and Wheat in Swedish Schoolchildren: A Population Based Cohort Study

Abstract: ObjectivesKnowledge about the prevalence of allergies to foods in childhood and adolescence is incomplete. The purpose of this study was to investigate the prevalence of allergies to milk, egg, cod, and wheat using reported data, clinical examinations, and double-blind placebo-controlled food challenges, and to describe the phenotypes of reported food hypersensitivity in a cohort of Swedish schoolchildren.MethodsIn a population-based cohort of 12-year-old children, the parents of 2612 (96% of invited) complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 37 publications
1
56
0
3
Order By: Relevance
“…The prevalence of challenge‐proven milk allergy was likely to be even lower. In a previous study of this cohort, about half of the children categorised as having a current allergy to milk, egg, cod or wheat had a positive double‐blind food challenge .…”
Section: Discussionmentioning
confidence: 86%
“…The prevalence of challenge‐proven milk allergy was likely to be even lower. In a previous study of this cohort, about half of the children categorised as having a current allergy to milk, egg, cod or wheat had a positive double‐blind food challenge .…”
Section: Discussionmentioning
confidence: 86%
“…However, considering the previously shown large discrepancies between parent-reported and diagnosed food allergies (2,(4)(5)(6)(7)(8)(9)16,17), and the fact that many children on special medical diets lack medical certificates, some children may have been subjected to unnecessarily restricted diets. A potential way to avoid this may be the requirement for mandatory medical certificates for special diets for medical reasons, preferably with an appropriate time limit, for example for cows' milk and hens' egg allergies.…”
Section: Discussionmentioning
confidence: 99%
“…There are large discrepancies between parent-reported and physician-diagnosed food hypersensitivity, which might lead to unnecessary diet restrictions with potential negative effects on nutrition during an important period of growth and development (2,(4)(5)(6)(7)(8)(9)(16)(17)(18)(19). Unnecessary special diets can also result in additional costs and efforts for families and the preschools and schools their children attend (20).…”
Section: Introductionmentioning
confidence: 99%
“…Most reports are based on self-reported food allergy, however, and it has been repeatedly shown that self-reported data will overestimate the prevalence as compared with evaluation by an oral food challenge [2][3][4] . It is estimated that IgE-mediated food allergy affects approximately 6-8% of children in developed countries [1,3,4] , thereby posing a significant burden on the afflicted children, their families, and the healthcare system.…”
Section: Introductionmentioning
confidence: 99%